Learning Analysis in the Physiology of Plant Growth and Development Practice through Schoology - Lina Agustina; Rivky Arif Rahmat (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2020)
Background: Schoology is an E-learning that can be a solution in an effort to create a fun learning process in the industrial era 4.0. One of the practice subjects in the Biology education FKIP UMS, whose learning through Schoology is Physiology of Plant Growth and Development. The purpose of this study was to determine the implementation of learning through Schoology in the physiology of plant growth and development practice, which includes: 1) archieved effectiveness of the plant growth and development physiology practice learning material; 2) student constraints during learning through schoology. Method: This type of research is a descriptive study with a qualitative approach. The sample in this study were 120 students taken using the Taro Yamane formula. Data collection techniques using questionnaires and interviews. Data were obtained from the results of questionnaires and interviews with 10 class representative students about the implementation of Schoology-based online practicum during the implementation of the plant growth and development physiology practice in the even semester. Results: The results showed that the average percentage was 67.07%, which means that learning through schoology in the plant growth and development physiology practice is effective, most of the obstacles experienced by students are signals, because not all regions have good signals.